Managing the process of catalytic reforming by the optimal distribution of temperature at the reactor block inlets - Левчук, Игорь Леонидович (Technology audit and production reserves, 2015)
In this paper it is investigated an influence of the temperature of the reaction mixture at the inlets of a catalytic reforming reactor block on increment of aromatic hydrocarbons at outlets of separate reactors. It is found that for each reactor of a catalytic reforming exists some optimal temperature of the initial mixture from the standpoint of the increment of aromatics, which does not exceed a noticeable increase of flavoring materials, however, increases the rate of deactivation of the catalyst due to the acceleration of hydrocracking reactions, contribute to the formation of coke on its surface. It is proposed the new method of finding the optimum point temperature at the reactor inlets, which provides optimum ratio of aromatization reactions and hydrocracking in reactors, depending on the desired rigidity of conducting the process. It is made a formulation of the problem of optimal control based on technical and economic analysis of the reforming unit of the Odessa refinery. A method to solve this problem based is proposed on the method of nonlinear Hooke-Jeeves optimization, supplemented by the procedure of border control of variable parameters. An algorithm for calculating the optimal process conditions and the control method based on it, which increases the yield of the desired product – the catalyzate an average of 3-5 %, which is confirmed by the results of experimental testing.